Hazard level of vehicle smoke by fuzzy multiple attribute decision making with simple additive weighting method - Abadi S.; Huda M.; Teh K.S.M.; Haroon Z.; Ripin M.N.; Hehsan A.; Sarip S.; Hehsan M.R.; Amrullah M.; Maseleno A. (Advanced Scientific Research, 2023)
carbon dioxide; carbon monoxide; nitrogen oxide; acid rain; air; air pollution; Article; brain damage; decision making; decision support system; eye irritation; fumigation; fuzzy multiple attribute decision making method; hazard assessment; human; lung disease; mathematical model; mental deficiency; motor vehicle; respiratory tract infection; semi structured interview; smoke; throat irritation; tobacco